Youth, Federalism, And Democratic Deepening in The Viksit Bharat Framework - Rohini Patil (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
India’s youth represent the country’s greatest strength, with a vibrant and dynamic generation driving the vision of making India a developed nation by 2047. Youth have the power to change the nation. Young minds will be fresher and more innovative which helps in the progress of the country. India’s Aspiration of becoming a Vikas it Bharat (developed nation) by 2047 depends on a robust federalism system and a vibrant democracy anchored in citizen’s participation with over 65% of its population below the age of 35. India’s youth constitute a powerful force in shaping democratic practices and strengthening federal governance. This Article investigates the role of youth in federalism and democratic deepening using the Vikas it Bharat frame work 2047 vision as a conceptual study it draws on the theories of participatory democracy, a cooperative federalism and youth political engagement to examine how young citizens contribute to democratic reliance and developmental aspirations. The paper concludes by offering policy directions to institutionalize youth participation in India’s democratic and federal journey towards 2047.